Jalan Damai Pemerintah Kota Bogor dalam Eskalasi Konflik 15 Tahun Rumah Ibadah GKI Yasmin - Alvina Kusuma; Agus Adriyanto; Syamsunasir Syamsunasir (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Indonesia is one of the countries of multi-ethnic, racial, tribal, language, culture, and religion. Religions and various schools thrive therefore the understanding of religious pluralism in pluralism is needed, one of which is often a problem in Indonesia is the establishment of houses of worship. The problem of establishing a house of worship or the transfer of the function of the use of buildings instead of houses of worship in an area can lead to horizontal conflict. GKI Yasmin conflict in Bogor City is one of the problems of the establishment of houses of worship in Indonesia. Polemic of the existence of GKI Yasmin began the rejection by 30 residents of Curug Mekar Village of Bogor City on January 10, 2006 they filed a letter to the Mayor of Bogor to revoke the IMB GKI Yasmin. The Yasmin GKI conflict lasted for 15 years from 2006 to 2021. The path of peace has been taken and both sides have agreed to the relocation of GKI Yasmin, conflict resolution by the Bogor city government received appreciation from the central government. This event is a message of peace from Bogor to the world that peace can never be achieved by judging each other.